Laboratory operando Fe and Mn K-edges XANES and Mössbauer studies of the LiFe0.5Mn0.5PO4 cathode material. (October 2020) - Shapovalov, V.V.; Guda, A.A.; Kosova, N.V.; Kubrin, S.P.; Podgornova, O.A.; Aboraia, A.M.; Lamberti, C.; Soldatov, A.V.
Abstract: We have developed and tested cell for laboratory operando diagnostics of Li-ion cathode materials. Local atomic and electronic structure of LiFe1-x Mnx PO4 olivine cathode was studied by means of Fe and Mn K-edges XAS and Mössbauer spectroscopy. Analysis of XAS data allows us to follow the structural and oxidation state changes occurring during the cell cycling. Together with operando Mössbauer spectroscopy sensitive to the fine Fe ions local coordination distortions escaping from laboratory XANES, we are able to prove the homogeneity of Fe and Mn ions distribution. Highlights: Developed the cell for operando XAS and Mössbauer measurements with laboratory equipment. Separated redox processes for Fe and Mn ions revealed in LeFe0.5 Mn0.5 PO4 cathode. Oxidation state and local structure changes for d-metal ions during (de)lithiation described. Homogeneous distribution of Fe and Mn ions in LeFe0.5 Mn0.5 PO4 was confirmed.